NYSDEC Raptor Tracking-reference-data - Nye, Peter; Hewitt, Glenn; Swenson, Theresa; Kays, Roland (Movebank Data Repository, 2018)
Nye P (2010) New York State bald eagle report 2010. New York State Department of Environmental Conservation, Albany, New York. 43 p. : Satellite telemetry collected between 1992 and 2010 by the New York State Department of Environmental Conservation to document the migratory pathways of raptors and owls in NY State.